Migrating to Windows phone - Liberty, Jesse; Blankenburg, Jeff (Apress, 2012)
This book offers everything you'll need to upgrade your existing programming knowledge and begin to develop applications for the Windows Phone. It focuses on the 75 percent of the material that you will need 95 percent of the time. We're not going to teach you object-oriented programming (OOP) all over again, but we are going to take the time to point out how .NET and C# differ in their execution of the standard OOP concepts from other languages' implementations in order to make your migration as smooth and stress-free as possible. Migrating to Windows Phone will lead you through a tour of the key features of developing for Microsoft's devices. We'll consider everything from data handling to accelerometers, from mapping to WCF. We'll also walk you through monetizing your application through Microsoft's online Windows Phone store.